QBO changes in CMIP6 climate projections - Butchart, N; Anstey, JA; Kawatani, Y; Osprey, SM; Richter, JH; Wu, T (American Geophysical Union, 2020)
Phase six of the Coupled‐Model Intercomparison Project (CMIP6) is the first in which a significant number of models include a well resolved stratosphere. Changes in equatorial stratospheric variability in historical and Shared Socioeconomic Pathways (SSPs) scenario simulations are investigated in ten models with realistic quasi‐biennial oscillations (QBO). All project a weakening of the QBO throughout the stratosphere for SSP370 and SSP585 scenarios and for 1960 to 2010. The weakening is strongest in the lower stratosphere, ranging from 5.8±0.5% through 4.3±0.5% to 2.0±0.5% per decade at 50 hPa for SSP585, SSP370 and historical simulations, respectively. At 20 hPa a weakening of both westward and eastward phases contributes though the weakening eastward phase is only seen in seven of the ten models. Similar robust weakening occurs for the temperature QBO, but only from 30 hPa upwards. In both scenarios the QBO period decreases in seven of the ten models.